Penerapan Model Pembelajaran Cooperative Numbered Head Together Untuk Meningkatkan Hasil Belajar Matematika - Susiani, Eka Titik; Hidayah, Shofia; Sutama, Edy (Papanda, 2025)
This study aims to improve mathematics learning outcomes in exponential material through the implementation of the Numbered Heads Together (NHT) cooperative learning model. The research employed a Classroom Action Research (CAR) method conducted in two cycles, with the research subjects being 25 students of class X-E at MAN 1 Probolinggo in the odd semester of the 2025/2026 academic year. Each cycle consisted of planning, action, observation, and reflection stages. Research instruments included learning outcome tests and learning activity questionnaires. The success indicator was established with a classical mastery criterion of at least 48% of students obtaining scores ≥75 according to the Minimum Mastery Criteria (KKM). The results showed a gradual increase in learning mastery, namely in the pre-cycle mastery was 0%, cycle I increased to 24% (6 students), and cycle II reached 48% (12 students). This improvement indicates that the NHT model is effective in creating active, collaborative, and student-centered learning. Students demonstrated positive changes in learning activities, courage to ask questions, and group discussion abilities. It can be concluded that the implementation of the Numbered Heads Together learning model is an effective alternative for improving mathematics learning outcomes in exponential material.